Hard carbon material and method of making, electrode and battery

CN122930909APending Publication Date: 2026-10-16HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611247559.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,外加硫容易形成游离硫或高表面硫,可能增加电解液副反应;强酸磺化需要洗涤并产生酸性废液;盐活化和模板法引入灰分、腐蚀及复杂后处理

Benefits of technology

[0016] The hard carbon material provided in this application is doped with an appropriate amount of sulfur, with the sulfur content controlled between 0.15wt% and 3wt%. This is due to the use of sulfur-containing pitch, a raw material with a high intracyclic sulfur content, which makes it easier for the sulfur in the intracyclic sulfur to bond with carbon, thus retaining the sulfur in the hard carbon. The retained sulfur can, on the one hand, introduce polar sodium storage sites through sulfur atoms, increasing the sodium storage capacity and adjusting the local electronic structure of the carbon skeleton, thereby improving the adsorption/intercalation capacity and charge transfer kinetics of sodium ions; on the other hand, it avoids the increase of surface side reactions caused by excessive sulfur content, thus balancing capacity improvement and interface stability. Meanwhile, the hard carbon material has an average pore size of 0.8nm to 3.0nm and a single-point pore volume of 0.06cm³/g to 0.22cm³/g, indicating that it has a rich and controlled pore structure. This pore structure is beneficial for providing storage space for sodium ions, especially for improving the low-voltage plateau capacity. Furthermore, since closed pores are not easily fully wetted by the electrolyte, it can reduce electrolyte decomposition and SEI film consumption caused by excessive open pores, thus improving specific capacity. In addition, the Raman I emission of the hard carbon material... D /I G A value ≥ 0.8 indicates high disorder and numerous defect sites, which can suppress excessive ordering of the carbon layer, increase sodium ion adsorption sites and transport channels, and improve the sodium storage capacity and rate performance of the material. In summary, through the synergistic confinement of sulfur doping, microporous/closed-pore structure, and high disorder, this hard carbon material can improve reversible sodium storage capacity and rate performance while reducing surface side reactions and improving specific capacity, making it suitable as a negative electrode material for sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930909A_ABST
    Figure CN122930909A_ABST
Patent Text Reader

Abstract

The application discloses a hard carbon material and a preparation method thereof, an electrode and a battery, and relates to the technical field of new energy sources.The hard carbon material satisfies the following conditions: the hard carbon material is doped with sulfur, and the content of the sulfur is 0.15wt%-3wt%; the average pore diameter of the hard carbon material is 0.8nm-3nm, and the single-point pore volume is 0.06cm3 / g-0.22cm3 / g; and the Raman I D / I G value of the hard carbon material is greater than or equal to 0.8.The hard carbon material disclosed by the application can increase sodium storage active sites and sodium ion transmission channels, improve reversible sodium storage capacity and rate performance through the synergistic cooperation of appropriate and stable sulfur doping, a suitable pore structure and a higher degree of disorder; meanwhile, the hard carbon material can reduce electrolyte side reactions and SEI film consumption, improve specific capacity, cycle stability and electrode processing performance, and is thus suitable for being used as a negative electrode material of a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, and in particular to a hard carbon material and its preparation method, electrodes and batteries. Background Technology

[0002] Asphalt has the advantages of high aromaticity, wide availability, high residual carbon content and suitability for large-scale continuous heat treatment, making it an important carbon source for the preparation of hard carbon anode materials. However, unstabilized asphalt is prone to softening, melting and fusing during the heating process, and undergoing orderly rearrangement of molecular layers. Ultimately, it tends to form a soft carbon structure with small interlayer spacing, defects and insufficient closed pores, which limits the reversible sodium storage capacity and rate performance.

[0003] In related technologies, air pre-oxidation, external sulfur crosslinking, sulfuric acid sulfonation, salt activation, template pore formation, or heteroatom doping are commonly used to suppress graphitization and increase sodium storage sites. However, external sulfur readily forms free sulfur or high surface sulfur, which may increase electrolyte side reactions; strong acid sulfonation requires washing and generates acidic waste liquid; salt activation and template methods introduce ash, corrosion, and complex post-processing. Furthermore, while simply increasing defects and open pores can improve ramp capacity and apparent kinetics, it often comes at the cost of increased specific surface area and decreased initial coulombic efficiency. To balance capacity, initial efficiency, and kinetics, synergistic control needs to be established among precursor crosslinking, sulfur retention / removal, open-pore to closed-pore conversion, and surface chemistry.

[0004] Therefore, the hard carbon materials with suitable sulfur structures obtained from asphalt preparation require further research and improvement. Summary of the Invention

[0005] In view of this, this application provides a hard carbon material and its preparation method, an electrode, and a battery.

[0006] The embodiments of this application are implemented as follows: Firstly, the embodiments of this application provide a hard carbon material, wherein the hard carbon material satisfies the following conditions: The hard carbon material is doped with sulfur, and the sulfur content is 0.15wt%~3wt%. The hard carbon material has an average pore size of 0.8 nm to 3 nm and a single-point pore volume of 0.06 cm³ / g to 0.22 cm³ / g. Raman 1 of the hard carbon material D / I G Value ≥ 0.8.

[0007] Optionally, in some embodiments of this application, the Raman spectroscopy of the hard carbon material is... D / I G The value is 0.8~1.5; The average particle size D of the hard carbon material v50 The range is from 2μm to 20μm; The average interlayer spacing of the hard carbon material is 0.37 nm to 0.42 nm; The specific surface area of ​​the hard carbon material is 1.0 m² / g to 8.0 m² / g; The true density of the hard carbon material is ≥0.7 g / cm³.

[0008] Optionally, in some embodiments of this application, the sulfur content of the hard carbon material increases from the outside to the inside within a thickness range of 0 nm to 200 nm.

[0009] Secondly, embodiments of this application also provide a method for preparing a hard carbon material, comprising the following steps: The sulfur-containing asphalt is provided, wherein the sulfur content of the sulfur-containing asphalt is 0.8% to 10%, and wherein the intracyclic sulfur accounts for 70% to 95% of the total sulfur by mass in the sulfur-containing asphalt; The sulfur-containing asphalt is subjected to a series of treatments, including pre-oxidation, low-temperature carbonization, and high-temperature carbonization, with the temperature increasing sequentially, to obtain the hard carbon material.

[0010] Optionally, in some embodiments of this application, the residual carbon content of the sulfur-containing asphalt is ≥40%; The softening point of the sulfur-containing asphalt is 100℃~300℃; The ash content of the sulfur-containing asphalt is ≤5%; The magnetic content of the sulfur-containing asphalt is ≤10ppm.

[0011] Optionally, in some embodiments of this application, the method for preparing sulfur-containing bitumen includes: Provide sulfur-containing oil products, wherein the sulfur content of the sulfur-containing oil products is 0.88% to 10%; The sulfur-containing oil is subjected to heat treatment to obtain the sulfur-containing asphalt.

[0012] Optionally, in some embodiments of this application, the sulfur-containing oil may include one or more of high-sulfur residue oil, high-sulfur slurry oil, high-sulfur wax oil, and high-sulfur coal tar. The heat treatment is carried out in an oxygen-containing atmosphere; The heat treatment includes: a preheating treatment and a reaction heat treatment performed in sequence with progressively increasing temperatures; the temperature of the preheating treatment is 100℃~200℃, and the time of the preheating treatment is 1h~3h; the temperature of the reaction heat treatment is 250℃~350℃, and the time of the reaction heat treatment is 2h~5h.

[0013] Optionally, in some embodiments of this application, the pre-oxidation treatment includes introducing oxygen-containing gas at a volumetric flow rate of 5 L to 20 L / min; the temperature of the pre-oxidation treatment is 200°C to 300°C; and the time of the pre-oxidation treatment is 3 h to 20 h. The temperature of the low-temperature carbonization treatment is 400℃~700℃, and the time of the low-temperature carbonization treatment is 0.5h~4h; The high-temperature carbonization treatment is carried out at a temperature of 1100℃ to 1400℃ for a duration of 0.5h to 4h.

[0014] Thirdly, embodiments of this application also provide an electrode, the material of which includes the hard carbon material described above, or a hard carbon material prepared by the method described above for preparing hard carbon material.

[0015] Fourthly, embodiments of this application also provide a battery, including a negative electrode, wherein the material of the negative electrode includes the aforementioned hard carbon material, or the material of the negative electrode includes hard carbon material prepared by the aforementioned method for preparing hard carbon material, or the negative electrode includes the aforementioned electrode.

[0016] The hard carbon material provided in this application is doped with an appropriate amount of sulfur, with the sulfur content controlled between 0.15wt% and 3wt%. This is due to the use of sulfur-containing pitch, a raw material with a high intracyclic sulfur content, which makes it easier for the sulfur in the intracyclic sulfur to bond with carbon, thus retaining the sulfur in the hard carbon. The retained sulfur can, on the one hand, introduce polar sodium storage sites through sulfur atoms, increasing the sodium storage capacity and adjusting the local electronic structure of the carbon skeleton, thereby improving the adsorption / intercalation capacity and charge transfer kinetics of sodium ions; on the other hand, it avoids the increase of surface side reactions caused by excessive sulfur content, thus balancing capacity improvement and interface stability. Meanwhile, the hard carbon material has an average pore size of 0.8nm to 3.0nm and a single-point pore volume of 0.06cm³ / g to 0.22cm³ / g, indicating that it has a rich and controlled pore structure. This pore structure is beneficial for providing storage space for sodium ions, especially for improving the low-voltage plateau capacity. Furthermore, since closed pores are not easily fully wetted by the electrolyte, it can reduce electrolyte decomposition and SEI film consumption caused by excessive open pores, thus improving specific capacity. In addition, the Raman I emission of the hard carbon material... D / I G A value ≥ 0.8 indicates high disorder and numerous defect sites, which can suppress excessive ordering of the carbon layer, increase sodium ion adsorption sites and transport channels, and improve the sodium storage capacity and rate performance of the material. In summary, through the synergistic confinement of sulfur doping, microporous / closed-pore structure, and high disorder, this hard carbon material can improve reversible sodium storage capacity and rate performance while reducing surface side reactions and improving specific capacity, making it suitable as a negative electrode material for sodium-ion batteries. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a flowchart illustrating a method for preparing a hard carbon material according to an embodiment of this application; Figure 2 This is the XPS S 2p spectrum of the sulfur-containing asphalt in Example 1 of the hard carbon material of this application. Detailed Implementation

[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.

[0020] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the orientation shown in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.

[0021] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0022] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0023] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0024] In this application, the term "numerical interval" (i.e., numerical range) is used. Unless otherwise specified, the distribution of selectable numerical values ​​within the numerical interval is considered continuous, and includes the two endpoints (i.e., the minimum and maximum values) of the numerical interval, as well as every value between these two endpoints. Unless otherwise specified, when the numerical interval refers only to integers within the numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include numerical interval types such as percentage intervals, ratio intervals, and proportion intervals.

[0025] Unless otherwise specified, the temperature parameters in this application may be either constant temperature treatment or variations within a certain temperature range. It should be understood that the constant temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.

[0026] In this invention, the term "room temperature" or "normal temperature" generally refers to 4℃~35℃, for example, 20℃±5℃. In some embodiments of this invention, "room temperature" or "normal temperature" refers to 10℃~30℃. In some embodiments of this invention, "room temperature" or "normal temperature" refers to 20℃~30℃.

[0027] The technical solution of this application is as follows: In a first aspect, embodiments of this application provide a hard carbon material. The hard carbon material satisfies the following conditions: the hard carbon material is doped with sulfur, and the sulfur content is 0.15wt%~3wt%; the average pore size of the hard carbon material is 0.8nm~3nm, and the single-point pore volume is 0.06cm³ / g~0.22cm³ / g; the Raman spectroscopy of the hard carbon material... D / I G Value ≥ 0.8.

[0028] It should be noted that the sulfur content of the hard carbon material was obtained by ICP (inductively coupled plasma atomic emission spectrometry) microwave digestion method.

[0029] The average pore size and single-point pore volume of the hard carbon material were obtained using the BET (Brunauer–Emmett–Teller) nitrogen adsorption test method. The single-point pore volume typically refers to the pore volume calculated at a specified relative pressure point (P / P0=1) during the nitrogen adsorption / desorption test.

[0030] Raman 1 of the hard carbon material D / I G The values ​​were obtained using Raman spectroscopy. Specifically, Raman spectroscopy was performed on hard carbon materials, and the values ​​were found to be around 1350 cm⁻¹. - ¹Near the D peak and approximately 1580 cm - For the G peak near ¹, calculate the ratio of their peak intensities or peak areas, i.e., I. D / I G The characterization meanings are as follows: the D peak mainly reflects defects, disordered structures, and edge sites in carbon materials; the G peak mainly reflects the ordered vibrations of sp² carbon atoms in the graphitized carbon layer. D / I G A higher value usually indicates a higher degree of defect or disorder in the hard carbon material and a lower degree of graphitization.

[0031] The hard carbon material provided in this application is doped with an appropriate amount of sulfur, with the sulfur content controlled between 0.15wt% and 3wt%. This is due to the use of sulfur-containing pitch, a raw material with a high intracyclic sulfur content, which makes it easier for the sulfur in the intracyclic sulfur to bond with carbon, thus retaining the sulfur in the hard carbon. The retained sulfur can, on the one hand, introduce polar sodium storage sites through sulfur atoms, increasing the sodium storage capacity and adjusting the local electronic structure of the carbon skeleton, thereby improving the adsorption / intercalation capacity and charge transfer kinetics of sodium ions; on the other hand, it avoids the increase of surface side reactions caused by excessive sulfur content, thus balancing capacity improvement and interface stability. Meanwhile, the hard carbon material has an average pore size of 0.8nm to 3.0nm and a single-point pore volume of 0.06cm³ / g to 0.22cm³ / g, indicating that it has a rich and controlled pore structure. This pore structure is beneficial for providing storage space for sodium ions, especially for improving the low-voltage plateau capacity. Furthermore, since closed pores are not easily fully wetted by the electrolyte, it can reduce electrolyte decomposition and SEI film consumption caused by excessive open pores, thus improving specific capacity. In addition, the Raman I emission of the hard carbon material... D / I GA value ≥ 0.8 indicates high disorder and numerous defect sites, which can suppress excessive ordering of the carbon layer, increase sodium ion adsorption sites and transport channels, and improve the sodium storage capacity and rate performance of the material. In summary, through the synergistic confinement of sulfur doping, microporous / closed-pore structure, and high disorder, this hard carbon material can improve reversible sodium storage capacity and rate performance while reducing surface side reactions and improving specific capacity, making it suitable as a negative electrode material for sodium-ion batteries.

[0032] In some embodiments, the sulfur content of the hard carbon material can be 0.15%, 0.5%, 1%, 1.5%, 2%, 3%, or any range between two of the above values. Appropriate sulfur doping can increase sodium storage sites and improve reversible sodium storage capacity and rate performance.

[0033] In some embodiments, the average pore size of the hard carbon material can be 0.8 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, or any two of the above values. A suitable average pore size is beneficial for forming microporous sodium storage spaces, while avoiding excessive electrolyte wetting and increased side reactions caused by excessively large pore sizes.

[0034] In some embodiments, the single-point pore volume of the hard carbon material can be 0.06 cm³ / g, 0.08 cm³ / g, 0.10 cm³ / g, 0.15 cm³ / g, 0.18 cm³ / g, 0.22 cm³ / g, or any range between two of the above values. A suitable single-point pore volume can provide effective adsorption, intercalation, or filling space for sodium ions, increasing sodium storage active sites and improving the transport path of sodium ions within the hard carbon material. Simultaneously, an excessively high pore volume can avoid excessive electrolyte wetting, continuous SEI film formation, and a decrease in specific capacity due to too many open pores.

[0035] In some embodiments, the Raman 1 of the hard carbon material D / I G The value can be between 0.8 and 1.5, for example, it can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.5, or any range between two of the above values. The Raman I... D / I G A relatively large value indicates that hard carbon materials have a high degree of disorder and a large number of defect sites, which is beneficial to suppressing excessive ordering of carbon layers and improving sodium ion storage and transport performance.

[0036] In some embodiments, the average particle size D of the hard carbon material v50The average particle size is between 2 μm and 20 μm, for example, it can be 2 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, or any range between two of the above values. A suitable average particle size is beneficial for balancing material processing performance, electrode compaction performance, and sodium ion transport pathways, thereby improving the overall electrochemical performance of the anode material. It should be noted that the average particle size of the hard carbon material was obtained using a laser particle size analyzer.

[0037] In some embodiments, the average interlayer spacing of the hard carbon material is 0.37 nm to 0.42 nm, for example, it can be 0.37 nm, 0.38 nm, 0.39 nm, 0.40 nm, 0.41 nm, 0.42 nm, or any range between two of the above values. The average interlayer spacing of the hard carbon material is larger than that of conventional graphite, which is beneficial for expanding the sodium ion insertion and transport channels, and improving the reversible sodium storage capacity and rate performance of the hard carbon material. It should be noted that the average interlayer spacing of the hard carbon material refers to the average distance between adjacent carbon layers in the hard carbon material, which is obtained by X-ray diffraction (XRD).

[0038] In some embodiments, the specific surface area of ​​the hard carbon material is 1.0 m² / g to 8.0 m² / g, for example, it can be 1.0 m² / g, 2.0 m² / g, 3.5 m² / g, 5.0 m² / g, 6.5 m² / g, 8.0 m² / g, or any range between two of the above values. Within this specific surface area range, it is beneficial to provide effective sodium storage active sites, while avoiding an excessively high specific surface area that would lead to increased electrolyte side reactions and decreased specific capacity. It should be noted that the specific surface area of ​​the hard carbon material is obtained using the BET (Brunauer–Emmett–Teller) test method.

[0039] In some embodiments, the true density of the hard carbon material is ≥0.7 g / cm³. Further, the true density of the hard carbon material is between 0.7 g / cm³ and 3 g / cm³, for example, it can be 0.7 g / cm³, 0.8 g / cm³, 0.9 g / cm³, 1.0 g / cm³, 1.2 g / cm³, 1.5 g / cm³, 2 g / cm³, 3 g / cm³, or any range between two of the above values. A suitable true density is beneficial for improving the structural stability and electrode compaction performance of the hard carbon material, thereby enhancing the energy density and cycle stability of the anode material. It should be noted that the true density of the hard carbon material is obtained by testing with a true density meter.

[0040] In some embodiments, the sulfur content of the hard carbon material increases from 0 nm to 200 nm in thickness from the outside to the inside. In other words, the hard carbon material has a sulfur-poor surface and sulfur-rich interior structure, which is beneficial for balancing interfacial stability and bulk sodium storage performance. On the one hand, the lower surface sulfur content can reduce side reactions between surface active sulfur or unstable sulfur and the electrolyte, reduce excessive SEI film formation and irreversible sodium consumption, thereby improving specific capacity and cycle stability. On the other hand, the sulfur-rich interior allows more sulfur to be retained inside the carbon framework, forming stable sodium storage active sites in the form of covalent sulfur, etc., and regulating the local electronic structure, inducing carbon layer bending or dislocation, expanding the interlayer channels accessible to sodium ions, thereby improving reversible sodium storage capacity, rate performance, and reaction kinetics. Therefore, the gradient distribution of sulfur-poor surface and sulfur-rich interior can enhance the internal sodium storage capacity of the material while reducing interfacial side reactions. In this application, the variation law of sulfur content within a certain thickness range is obtained by etching different thicknesses with XPS to test the sulfur content of the corresponding interfaces, and then recording the sulfur content data.

[0041] It should be noted that the term "incremental" in this application should be interpreted broadly, meaning that along the outer surface of the hard carbon material toward its core center, within a defined thickness range of 0 nm to 200 nm, the sulfur content at each interface can increase stepwise (in segments or intervals) or continuously, and the rate of continuous increase can vary, either continuously at a uniform rate or continuously at a variable rate.

[0042] Secondly, please refer to Figure 1 This application also provides a method for preparing a hard carbon material, which can prepare the above-mentioned hard carbon material. The method for preparing the hard carbon material includes the following steps: Step S11: Provide sulfur-containing asphalt, wherein the sulfur content of the sulfur-containing asphalt is 0.8%~10%, and the intracyclic sulfur in the sulfur-containing asphalt accounts for 70%~95% of the total sulfur by mass. Step S12: The sulfur-containing asphalt is subjected to a pre-oxidation treatment, a low-temperature carbonization treatment, and a high-temperature carbonization treatment in sequence with increasing temperatures to obtain the hard carbon material.

[0043] It should be noted that the term "intracyclic sulfur" refers to sulfur-containing organic compounds and / or sulfur-containing functional groups in which sulfur atoms are located within a cyclic framework. Intracyclic sulfur includes aromatic heterocyclic sulfur, which includes one or more of aromatic conjugated five-membered ring sulfur and aromatic conjugated six-membered ring sulfur. As examples, aromatic heterocyclic sulfur includes thiophene, thiazole, thiaran, benzothiophene, dibenzothiophene, etc. These types of sulfur are relatively stable in their bonding with the carbon framework and have high thermal stability. In this application, the mass fraction of intracyclic sulfur to total sulfur is obtained by peak fitting test using X-ray photoelectron spectroscopy (XPS).

[0044] It should also be noted that "low temperature" and "high temperature" in low-temperature carbonization and high-temperature carbonization are relative terms. As mentioned above, "temperature increases sequentially" is only used to indicate that the temperature of high-temperature carbonization is higher than that of low-temperature carbonization, and there is no issue of unclear limitation.

[0045] This application utilizes sulfur-containing asphalt with high sulfur content, where sulfur primarily exists in the form of intracyclic sulfur, to prepare hard carbon materials through sequential pre-oxidation, low-temperature carbonization, and high-temperature carbonization treatments. Firstly, the high proportion of intracyclic sulfur in the total sulfur content indicates that the sulfur in the sulfur-containing asphalt exists primarily in a form stably bonded to the aromatic carbon skeleton, rather than as free sulfur, inorganic sulfur, or weakly bound sulfur. This type of intracyclic sulfur exhibits high thermal stability and is less prone to significant volatilization or migration to the material surface during pre-oxidation and carbonization. This facilitates the retention of sulfur within the carbon skeleton, forming stable covalent sulfur doping sites, thereby inducing carbon layer bending and dislocation, expanding local interlayer spacing, and increasing the availability of sodium ions. The sulfur-containing asphalt achieves interlayer channels and polar adsorption sites. Simultaneously, it can regulate the local electronic structure, improve charge transfer and reaction kinetics. Compared to free sulfur or surface-enriched sulfur, a higher proportion of intracyclic sulfur can reduce electrolyte side reactions and excessive SEI film consumption, which is beneficial for improving the reversible sodium storage capacity, rate performance, specific capacity, and cycle stability of hard carbon materials. Secondly, this sulfur-containing asphalt, through a three-stage coupling process of "pre-oxidation and sulfur fixation crosslinking—low-temperature carbonization and selective desulfurization—high-temperature carbonization and pore-closed reconstruction," inhibits asphalt ordering, constructs a multi-scale structure suitable for sodium ion adsorption, interlayer insertion, and pore filling, while controlling surface sulfur and open pores, reducing irreversible interfacial reactions. This application does not rely on external sulfur sources or strong acid sulfonation, which can reduce free sulfur, pickling waste liquid, metal residues and complex post-treatment. Moreover, it utilizes the synergistic cross-linking of endogenous sulfur and oxygen in the raw material during the pre-oxidation stage to improve thermosetting and carbon yield and inhibit asphalt ordering. Furthermore, it controls transient pores, defects and particle integrity by regulating the slow release of weak sulfur species and oxygen-containing groups through an independent low-temperature carbonization window. In addition, the high-temperature carbonization treatment retains a low content of covalent sulfur, in which surface sulfur forms a porous structure through volatilization and internal sulfur is stored internally, thereby forming a surface sulfur-poor / internal sulfur-rich gradient, which improves bulk sodium storage and kinetics while reducing interfacial side reactions.

[0046] Specifically, in the pre-oxidation stage, the aromatic rings, thioethers and fused thiophene sites adjacent to the endogenous sulfur in the sulfur-containing asphalt, together with the oxygen-containing functional groups, enhance the reactivity. The sulfur bridges / sulfur-containing aromatic nodes, together with the oxygen bridges, increase the intermolecular crosslinking, thereby increasing the softening point and thermosetting properties, inhibiting particle melting and the growth of the mesophase, increasing the residual carbon rate, and providing a stable template for the subsequent disordered framework and closed pores.

[0047] During the low-temperature carbonization stage, the weakly bound sulfur, aliphatic side chains, and some oxygen-containing groups in the sulfur-containing asphalt selectively decompose, generating controlled gas escape. Stable thiophene / fused thiophene sulfur is retained in the skeleton, thereby establishing short-range mass transfer channels and defect boundaries, avoiding a one-step increase to high temperature that would cause violent gas release, uncontrolled pores, or particle cracking; and forming transient pores that can close at high temperatures.

[0048] During the high-temperature carbonization stage, the residual covalent sulfur in sulfur-containing asphalt acts as a large, polarizable heteroatom site, inducing carbon layer bending, dislocation, and local interlayer spacing increase. At the same time, the high temperature promotes the preferential removal of unstable sulfur on the outer surface, thereby increasing the interlayer channels and polar adsorption sites accessible to sodium ions, improving the local electronic structure and charge transfer, promoting the partial closure of open pores, increasing the low-voltage plateau capacity, and reducing SEI consumption.

[0049] In step S11: In some embodiments, the sulfur content of the sulfur-containing asphalt can be, for example, 0.8%, 0.85%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range between any two of the above values. A suitable range of sulfur content allows for the introduction of appropriate amounts and forms of sulfur into hard carbon materials to improve their performance. It should be noted that the sulfur content of the sulfur-containing asphalt is obtained by ICP microwave digestion using a sulfur analyzer.

[0050] In some embodiments, the mass fraction of intracyclic sulfur to total sulfur can be, for example, 70%, 75%, 80%, 85%, 90%, 95%, or any range between two of the above values. This allows sulfur to remain within the carbon framework in a thermally stable form, forming stable covalent sulfur doping sites, thereby reducing surface side reactions and improving the reversible sodium storage capacity, rate performance, and cycle stability of hard carbon materials.

[0051] In some embodiments, the residual carbon content of the sulfur-containing asphalt is ≥40%, and more specifically, the residual carbon content of the sulfur-containing asphalt is 40%~80%. For example, it can be 40%, 45%, 50%, 55%, 60%, 70%, 80%, or a range between any two of the above values. A higher residual carbon content is beneficial for improving the carbon yield of the sulfur-containing asphalt in the subsequent carbonization process, reducing raw material loss, and enhancing the cost advantage of hard carbon material preparation. It should be noted that the residual carbon content of the sulfur-containing asphalt can be obtained by thermogravimetric analysis, for example, by performing a TGA test under a nitrogen protective atmosphere, and calculated as the ratio of the final residual carbide mass to the initial sulfur-containing asphalt mass.

[0052] In some embodiments, the softening point of the sulfur-containing asphalt is 100℃~300℃, for example, it can be 100℃, 120℃, 150℃, 180℃, 200℃, 250℃, 300℃, or any range between two of the above values. A suitable softening point is beneficial to ensure that the sulfur-containing asphalt has appropriate thermal stability during the pre-oxidation and carbonization heating process, reducing premature melting and fusion, and facilitating the formation of a stable hard carbon precursor structure. It should be noted that the softening point of the sulfur-containing asphalt can be obtained by testing according to GB / T4507-2014 "Asphalt Softening Point Determination Method - Ring and Ball Method".

[0053] In some embodiments, the ash content of the sulfur-containing asphalt is ≤5%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 5%, or any range between two of the above values. Lower ash content helps reduce the residue of inorganic impurities in hard carbon materials, thus reducing the negative impact of impurities on electrochemical performance and battery safety. It should be noted that the ash content of the sulfur-containing asphalt can be obtained according to SH / T 0422-2000 "Determination of Ash Content in Asphalt".

[0054] In some embodiments, the magnetic material content of the sulfur-containing asphalt is ≤10 ppm. The magnetic material content of the sulfur-containing asphalt can be, for example, 0.1 ppm, 0.5 ppm, 1 ppm, 2 ppm, 5 ppm, 10 ppm, or any range between two of the above values. A lower magnetic material content helps reduce the impact of metallic impurities such as iron, nickel, and chromium on battery self-discharge, short-circuit risk, and cycle stability, thereby improving the electrochemical reliability of the hard carbon anode material. It should be noted that the magnetic material content of the sulfur-containing asphalt can be obtained using inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0055] In some embodiments, the method for preparing sulfur-containing asphalt includes: Provide sulfur-containing oil products, wherein the sulfur content of the sulfur-containing oil products is 0.88% to 10%; The sulfur-containing oil is subjected to heat treatment to obtain the sulfur-containing asphalt.

[0056] In some embodiments, the sulfur-containing oil product may include one or more of high-sulfur residue, high-sulfur slurry oil, high-sulfur wax oil, and high-sulfur coal tar. It is understood that high-sulfur residue is a byproduct of petroleum processing, inexpensive, readily available commercially, widely sourced, and capable of high-performance utilization. Specifically, high-sulfur residue includes one or more of high-sulfur catalytic cracking residue, high-sulfur vacuum residue, and high-sulfur thermal cracking residue. High-sulfur vacuum residue is produced by heating atmospheric residue (a byproduct of oil refining) to 400°C-425°C in a vacuum furnace, followed by a high-vacuum vacuum distillation column. The low pressure lowers the boiling point of hydrocarbons, and vaporizable vacuum wax oil (heavy diesel, catalytic cracking / hydrocracking feedstock) from the atmospheric residue is extracted via a side stream. The heaviest fraction that cannot be vaporized at the bottom of the column is the high-sulfur vacuum residue.

[0057] In some embodiments, the sulfur content of the sulfur-containing oil can be, for example, 0.88%, 1%, 2%, 3%, 4%, 5%, 8%, 10%, or a range between any two of the above values. This application selects sulfur-containing oils with higher sulfur content, which can utilize the abundant sulfur element to prepare sulfur-containing asphalt with higher sulfur content.

[0058] In some embodiments, the heat treatment is carried out in an oxygen-containing atmosphere, which may be air or a pure oxygen atmosphere, etc.

[0059] In some embodiments, the heat treatment includes: a preheating treatment and a reaction heat treatment performed in sequence with progressively increasing temperatures.

[0060] In some embodiments, the preheating temperature is 100℃~200℃, for example, it can be 100℃, 120℃, 150℃, 180℃, 200℃, or any range between two of the above values; the preheating time is 1h~3h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, or any range between two of the above values. Thus, under the preheating conditions, moisture and some light components in the sulfur-containing oil slurry can be removed, and the system temperature gradually increases, which helps to reduce the risk of local overheating and violent component escape during subsequent reaction heat treatment, and provides a more stable pretreatment basis for subsequent oxidative crosslinking reactions.

[0061] In some embodiments, the temperature of the reaction heat treatment is 250℃~350℃, for example, it can be 250℃, 280℃, 300℃, 320℃, 350℃, or any range between two of the above values; the time of the reaction heat treatment is 2h~5h, for example, it can be 2h, 2.5h, 3h, 4h, 5h, or any range between two of the above values. Thus, under the conditions of the reaction heat treatment, the active components in the sulfur-containing oil slurry can further undergo oxidation, condensation, and cross-linking reactions, resulting in a moderate increase in molecular weight and the formation of a sulfur-containing asphalt structure; simultaneously, it further removes light components, improving the thermal stability and residual carbon content of the sulfur-containing asphalt, which is beneficial for the subsequent preparation of structurally stable sulfur-containing hard carbon materials.

[0062] In some embodiments, after the heat treatment, the material can be cooled to 150°C~300°C and discharged to obtain the desired sulfur-containing asphalt.

[0063] In step S12: It should be noted that the pre-oxidation treatment is carried out in an oxygen-containing atmosphere, while the low-temperature carbonization treatment and high-temperature carbonization treatment are carried out in an inert atmosphere such as nitrogen.

[0064] In some embodiments, before the sulfur-containing asphalt undergoes the pre-oxidation treatment, it further includes crushing to an average particle size D. v50 <1000μm. This ensures that the sulfur-containing asphalt is heated evenly, avoiding uneven heating inside and out.

[0065] In some embodiments, the pre-oxidation treatment includes introducing oxygen-containing gas at a flow rate of 5 L to 20 L / min, such as 5 L / min, 8 L / min, 10 L / min, 12 L / min, 15 L / min, 20 L / min, or any range between two of these values. A suitable oxygen-containing gas flow rate helps ensure sufficient contact between the sulfur-containing asphalt and oxygen during the pre-oxidation process, promoting the oxidative cross-linking reaction, while avoiding insufficient oxygen supply leading to incomplete pre-oxidation or excessive airflow causing material disturbance and uneven oxidation.

[0066] In some embodiments, the temperature of the pre-oxidation treatment is 200℃~300℃, for example, it can be 200℃, 220℃, 250℃, 280℃, 300℃, or any range between two of the above values; the time of the pre-oxidation treatment is 3h~20h, for example, it can be 3h, 5h, 8h, 10h, 15h, 20h, or any range between two of the above values. Thus, under the pre-oxidation treatment conditions, the endogenous sulfur and oxygen-containing functional groups in the sulfur-containing asphalt can synergistically promote intermolecular cross-linking and solidification, improve the thermal stability of the sulfur-containing asphalt, and inhibit melting and fusion and ordered rearrangement during subsequent heating processes.

[0067] In some embodiments, the temperature of the low-temperature carbonization treatment is 400℃~700℃, for example, it can be 400℃, 450℃, 500℃, 600℃, 700℃, or any range between two of the above values; the time of the low-temperature carbonization treatment is 0.5h~4h, for example, it can be 0.5h, 1h, 2h, 3h, 4h, or any range between two of the above values. Thus, under the conditions of the low-temperature carbonization treatment, weakly bound sulfur, aliphatic side chains, and some oxygen-containing groups can be selectively decomposed and escaped in a controlled manner, which is beneficial for forming defect boundaries and transient pore structures, while avoiding the violent outgassing, uncontrolled pore flow, or particle cracking caused by direct high-temperature carbonization.

[0068] It should be noted that, after the low-temperature carbonization treatment, the process further includes: pulverizing the low-temperature carbonization product obtained from the low-temperature carbonization treatment to an average particle size D. v50 The diameter is 2μm to 50μm to allow for more thorough high-temperature carbonization treatment later.

[0069] In some embodiments, the temperature of the high-temperature carbonization treatment is 1100℃~1400℃, for example, it can be 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1400℃ or any range between two of the above values; the time of the high-temperature carbonization treatment is 0.5h~4h, for example, it can be 0.5h, 1h, 2h, 3h, 4h or any range between two of the above values. Thus, under the conditions of the high-temperature carbonization treatment, some stable covalent sulfur can be retained in the carbon framework, while unstable sulfur on the outer surface is preferentially removed, which is beneficial for forming a hard carbon structure with low surface sulfur and rich internal sulfur, and promotes the partial closure of open pores, thereby improving sodium storage capacity, rate performance, and specific capacity.

[0070] This application selects sulfur-containing asphalt with high sulfur content and high intracyclic sulfur content as both a carbon source and a sulfur source. Under controlled pre-oxidation conditions, without the addition of external sulfur sources, strong acid sulfonating agents, metal salt activators, or sacrificial templates, it undergoes low-temperature carbonization and high-temperature carbonization treatments. The high proportion of intracyclic sulfur (such as thiophene sulfur) in the sulfur-containing asphalt is relatively stable in its combination with the aromatic carbon skeleton, and is less likely to volatilize or migrate to the material surface during heat treatment. This is beneficial for sulfur to remain within the carbon skeleton in a stable covalent sulfur form. Therefore, the endogenous sulfur in the sulfur-containing asphalt can promote cross-linking and curing during the pre-oxidation stage, regulate volatilization channels and defects during the low-temperature carbonization stage, and stabilize the disordered layered structure, induce carbon layer bending and dislocation, expand sodium ion transport channels, and regulate the local electronic structure after high-temperature carbonization using covalent sulfur sites. This results in a surface-depleted sulfur and internally rich sulfur structure, thereby reducing surface side reactions and SEI film consumption while improving the reversible sodium storage capacity, rate performance, specific capacity, and reaction kinetics of the hard carbon material.

[0071] Thirdly, embodiments of this application also provide an electrode, the material of which includes the aforementioned hard carbon material.

[0072] Fifthly, embodiments of this application also provide a battery, the battery including a negative electrode, the negative electrode being made of the aforementioned hard carbon material, or the negative electrode including the aforementioned electrode.

[0073] The battery may include, but is not limited to, lithium-ion batteries, sodium-ion batteries, etc.

[0074] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0075] Hard carbon material Example 1 This embodiment provides a hard carbon material, the preparation method of which includes the following steps: Step S21, Preparation of sulfur-containing asphalt: High-sulfur oil slurry (sulfur content of 3%) is put into a reaction vessel, stirred and distilled at 150°C for 2 hours to remove light components, and then heated to 300°C and stirred and distilled for 3 hours. During the heat treatment process, air is continuously introduced for oxidation. Then the air is replaced with nitrogen protective gas to stop the oxidation. The temperature is lowered to 200°C to cool and discharge the material to obtain sulfur-containing asphalt. Step S22, Pre-oxidation treatment: The sulfur-containing asphalt is coarsely crushed to D. v50 <1000μm, transfer to a rotary kiln, introduce air at 10L / min, and pre-oxidize at 250℃ for 5h; Step S23, Carbonization Treatment: The pre-oxidized sulfur-containing asphalt is heated to 600℃ in a box furnace under nitrogen atmosphere at a heating rate of 3℃ / min for low-temperature carbonization treatment, held at this temperature for 2 hours, and then naturally cooled to obtain the low-temperature carbonized product; the low-temperature carbonized product is then pulverized into D... v50 Fine powder with a particle size of about 30μm was placed again in a box furnace under nitrogen atmosphere and heated to 1200℃ at a heating rate of 3℃ / min for high-temperature carbonization treatment. The temperature was held for 2 hours. After carbonization, the powder was sieved and demagnetized to obtain hard carbon material.

[0076] Hard carbon material Example 2 This embodiment is basically the same as Embodiment 1, except that in step S21, the high-sulfur slurry oil (sulfur content of 3%) is replaced with high-sulfur vacuum residue oil (sulfur content of 5%).

[0077] Hard carbon material Example 3 This embodiment is basically the same as Embodiment 1, except that in step S21, the high-sulfur oil slurry (sulfur content of 3%) is replaced with high-sulfur coal tar (sulfur content of 8%).

[0078] Hard carbon material Example 4 This embodiment is basically the same as embodiment 1, except that in step S21, the two heat treatments of the high-sulfur oil slurry are replaced by one heat treatment: heat treatment at 250°C for 4 hours.

[0079] Hard carbon material Example 5 This embodiment is basically the same as embodiment 1, except that in step S22, the pre-oxidation treatment conditions are replaced with: pre-oxidation treatment at 200℃ for 10 hours.

[0080] Hard carbon material Example 6 This embodiment is basically the same as embodiment 1, except that in step S22, the pre-oxidation treatment conditions are replaced with: 300℃ pre-oxidation treatment for 3 hours.

[0081] Hard carbon material Example 7 This embodiment is basically the same as embodiment 1, except that in step S23, the low-temperature carbonization treatment conditions are replaced with: 400℃ low-temperature carbonization treatment for 4 hours.

[0082] Hard carbon material Example 8 This embodiment is basically the same as Embodiment 1, except that in step S23, the low-temperature carbonization treatment conditions are replaced with: 700℃ low-temperature carbonization treatment for 0.5h.

[0083] Hard carbon material Example 9 This embodiment is basically the same as embodiment 1, except that in step S23, the conditions for high-temperature carbonization are replaced with: high-temperature carbonization at 1100℃ for 4 hours.

[0084] Hard carbon material Example 10 This embodiment is basically the same as Embodiment 1, except that in step S23, the conditions for high-temperature carbonization are replaced with: high-temperature carbonization at 1400℃ for 0.5h.

[0085] Hard carbon materials comparative example 1 This comparative example is basically the same as Example 1, except that the sulfur-containing asphalt in step S21 is directly replaced with commercially available conventional asphalt with a sulfur content of less than 0.1%.

[0086] Hard carbon materials comparative example 2 This comparative example provides a hard carbon material, the preparation method of which includes the following steps: Step S31, Preparation of sulfur-containing asphalt: Asphalt with a softening point of 200℃ is mixed with sulfonating agent (concentrated sulfuric acid with a mass fraction of 98%) at a solid-liquid ratio of 1g:5mL. The mixture is stirred at a constant temperature of 80℃ for 4 hours and then the reaction is stopped. The mixture is then filtered, washed, dried and pulverized to obtain sulfur-containing asphalt. Step S32, Pre-oxidation treatment: The sulfur-containing asphalt powder is placed in an air atmosphere for pre-oxidation treatment. The temperature is increased to 250℃ at a heating rate of 3℃ / min and held for 4 hours. After the holding period, the material is cooled down with the furnace to obtain the pre-oxidized sulfur-containing asphalt. Step S33, Carbonization treatment: The sulfur-containing asphalt after pre-oxidation treatment is placed in a tube furnace under a high-purity argon atmosphere for high-temperature carbonization. The temperature is increased to 1200℃ at a heating rate of 3℃ / min and held for 2 hours to obtain hard carbon material.

[0087] Hard carbon materials comparative example 3 This comparative example provides a hard carbon material, the preparation method of which includes the following steps: Step S41, Preparation of sulfur-containing asphalt: Weigh coal tar pitch, elemental sulfur as the sulfur source, and terephthalaldehyde as the crosslinking agent and ball mill them together in a mass ratio of 1:3:3; Under argon protection, heat the mixture to 280℃ at a heating rate of 3℃ / min and hold for 3 hours to obtain sulfur-containing asphalt. Step S42, carbonization treatment: After grinding the sulfur-containing asphalt, it is heated to 1200℃ and held for 2 hours under argon atmosphere at a heating rate of 3℃ / min to obtain hard carbon material.

[0088] The sulfur content of the sulfur-containing asphalt in Example 1 of the hard carbon material was determined by X-ray photoelectron spectroscopy (XPS). Please refer to the obtained S2p spectrum. Figure 2 As shown. Among them, Figure 2 In the diagram, the blue lines represent organic thiophenes, the red lines represent organic sulfides, the black lines represent all sulfur compounds, and the purple lines represent the fitted curve.

[0089] Depend on Figure 2 It can be seen that the sulfur in the sulfur-containing asphalt in Example 1 mainly exists in the form of organic thiophene and organic sulfide (both of which belong to intracyclic sulfur).

[0090] The sulfur content, intracyclic sulfur percentage, residual carbon content, softening point, ash content, and magnetic material content of the sulfur-containing asphalt in Examples 1-4 and Comparative Examples 1-3 of hard carbon materials were tested. All test methods were the same as those for the parameters described above, and therefore will not be repeated here. The test results are shown in Table 1.

[0091] Table 1

[0092] As shown in Table 1: The embodiments of this application employ a suitable preparation method, resulting in sulfur-containing asphalt with appropriate sulfur content, high intracyclic sulfur content, high residual carbon rate, suitable softening point, and low ash and magnetic material content. This allows the sulfur-containing asphalt to balance raw material reactivity, thermal stability, carbon yield, and impurity control. Specifically, the appropriate sulfur content and high intracyclic sulfur ratio facilitate the participation of sulfur in subsequent pre-oxidation crosslinking and carbonization structure regulation in a more stable organic form, thereby forming suitable sulfur doping sites in the hard carbon material. The high residual carbon rate helps improve carbonization yield and reduce preparation costs. The suitable softening point helps suppress premature melting and fusion during heating, ensuring stable precursor transformation. The low ash and magnetic material content helps reduce inorganic and metallic impurities, mitigating their adverse effects on battery self-discharge, cycle stability, and safety performance. Therefore, the synergistic control of these parameters is beneficial for obtaining sulfur-containing hard carbon materials with stable structure, low impurity content, and excellent sodium storage performance.

[0093] Among them, the commercially available conventional asphalt in Comparative Example 1 has an extremely low sulfur content and no relevant data on sulfur content; Comparative Example 2 uses sulfonation treatment and Comparative Example 3 uses sulfurization treatment. Although sulfur is introduced, it uses an external sulfur source, making the preparation more complicated. Moreover, the proportion of sulfur in the ring is small, and there is less sulfur with higher stability and performance, which has limited improvement on the performance of hard carbon materials.

[0094] The total sulfur content, sulfur content at different thicknesses from the outside to the inside, average pore size, single-point pore volume, and Raman I of the hard carbon materials in Examples 1-10 and Comparative Examples 1-3 were tested. D / I G Value, average particle size D v50 The average interlayer spacing, specific surface area, and true density were all tested using the same methods as the parameters described above, and therefore will not be repeated here. For the total sulfur content and sulfur content at different thicknesses from the outside in, please refer to Table 2; for the remaining results, please refer to Table 3.

[0095] Table 2

[0096] Table 3

[0097] As can be seen from Tables 2 and 3: The hard carbon material prepared in this application exhibits suitable sulfur content, average pore size, single-point pore volume, and Raman spectroscopy performance. D / I G Value, average particle size D v50Under multiple parameter conditions, including average interlayer spacing, specific surface area, and true density, and by forming a sulfur-rich gradient structure with a sulfur-depleted surface and a sulfur-rich interior, the material can balance sodium storage sites, ion transport, interfacial stability, and electrode processing performance. Specifically, a suitable sulfur content is beneficial for introducing polar sodium storage sites and regulating the local electronic structure of the carbon framework. Furthermore, the material is prepared from sulfur-containing pitch with a high content of intracyclic sulfur, ensuring stable sulfur retention within the hard carbon material. Suitable average pore size and single-point pore volume facilitate the construction of a porous structure suitable for sodium ion adsorption, embedding, and closed-cell filling, improving reversible capacity and low-voltage plateau capacity. A higher Raman I value also contributes to this. D / I G The value indicates that the material has a high degree of disorder and a large number of defect sites, which is beneficial for suppressing excessive ordering of the carbon layer and increasing sodium storage active sites; the suitable average particle size D v50 These factors contribute to improved material processing performance and shortened sodium ion transport paths; a suitable average interlayer spacing facilitates sodium ion insertion and extraction between carbon layers; a suitable specific surface area provides active sites while reducing electrolyte side reactions and SEI film consumption; and a higher true density enhances material structural stability, electrode compaction performance, and volumetric energy density. The synergistic effect of these parameters leads to the development of hard carbon anode materials that combine high reversible sodium storage capacity, good rate performance, high specific capacity, and excellent cycle stability.

[0098] Since all hard carbon materials undergo the same crushing, sieving, and demagnetizing steps after preparation, D... v50 The results were consistent. Comparative Examples 2 and 3 introduced sulfur into the asphalt using an external sulfur source, but the amount of sulfur present in the form of stable intracyclic sulfur was relatively small. During the carbonization process into hard carbon materials, most of the sulfur failed to be stably retained, and the sulfur retained in the hard carbon materials had limited effect on improving the performance of the hard carbon materials, with low single-point pore volume and Raman I... D / I G It has a high value and a large specific surface area.

[0099] Battery Example 1 This embodiment provides a battery, including the following steps: The hard carbon material from Example 1 was mixed with styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and conductive carbon black (SP) in a ratio of 94.5:2.5:1.5:1.5. The mixture was prepared into a slurry with ultrapure water and coated onto an aluminum foil sheet. The resulting slurry coating was placed in a vacuum drying oven and dried at 90°C for 24 hours. After being pressed by a 5T roller, a circular electrode sheet with a diameter of 12 mm was pressed out using a tablet press to obtain the negative electrode of the experimental battery. A sodium sheet was used as the counter electrode, and a glass fiber disc was used as the separator. 1.0 mol / L NaPF6 was dissolved in an EC:DMC:EMC solvent (volume ratio of 1:1:1) as the electrolyte. Spring sheets and gaskets were added, and the battery was assembled into a 2032 model button cell in a glove box.

[0100] Battery Examples 2-10 Battery Examples 2-10 are basically the same as Battery Example 1, except that the hard carbon material in Hard Carbon Material Example 1 is replaced with the hard carbon material prepared in Hard Carbon Material Examples 2-10.

[0101] Battery Comparison 1~3 Battery Comparative Examples 1-3 are basically the same as Battery Example 1, except that the hard carbon material in Hard Carbon Material Example 1 is replaced with the hard carbon material prepared in Hard Carbon Material Comparative Examples 1-3.

[0102] Half-cell tests were conducted on the batteries of hard carbon materials and batteries Examples 1-10 and Comparative Examples 1-3 to obtain the specific capacity. The test results are shown in Table 4.

[0103] The specific capacity test method includes: testing with a blue electric test device in a constant temperature environment of 25℃, charging and discharging at a current density of 0.1C (1C=300 mA / g), and charging and discharging twice within a voltage range of 0.01V~2.00V. During the test, the second discharge specific capacity of each sodium-ion battery is obtained as the specific capacity.

[0104] Table 4

[0105] From Table 4, we can obtain: When the hard carbon material of this application is applied to sodium-ion batteries, suitable sulfur doping, disordered carbon layer structure, pore structure, interlayer spacing, specific surface area, and true density can synergistically improve the sodium storage behavior of the anode material. Specifically, sulfur doping and higher disorder are beneficial for increasing sodium storage active sites and improving charge transfer kinetics; suitable interlayer spacing and pore structure facilitate sodium ion insertion, adsorption, and pore filling; a lower and controlled specific surface area reduces electrolyte side reactions and SEI film consumption; and suitable particle size and true density improve electrode processing performance and compaction performance. Therefore, sodium-ion batteries incorporating this hard carbon material can exhibit high specific capacity.

[0106] Among them, Comparative Examples 2 and 3 introduced sulfur into asphalt by adding an external sulfur source to prepare hard carbon materials. The specific capacity of the battery was slightly improved compared with Comparative Example 1, which used conventional commercial asphalt, but it was still inferior to the battery performance of the battery embodiment of this application.

[0107] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A hard carbon material, characterized in that, The hard carbon material meets the following conditions: The hard carbon material is doped with sulfur, and the sulfur content is 0.15wt%~3wt%. The hard carbon material has an average pore size of 0.8 nm to 3 nm and a single-point pore volume of 0.06 cm³ / g to 0.22 cm³ / g. Raman 1 of the hard carbon material D / I G Value ≥ 0.

8.

2. The hard carbon material as described in claim 1, characterized in that, Raman 1 of the hard carbon material D / I G The value is 0.8~1.5; The average particle size D of the hard carbon material v50 The range is from 2μm to 20μm; The average interlayer spacing of the hard carbon material is 0.37 nm to 0.42 nm; The specific surface area of ​​the hard carbon material is 1.0 m² / g to 8.0 m² / g; The true density of the hard carbon material is ≥0.7 g / cm³.

3. The hard carbon material as described in claim 1, characterized in that, The sulfur content increases from the outside to the inside within the thickness range of 0nm to 200nm of the hard carbon material.

4. A method for preparing a hard carbon material, characterized in that, Includes the following steps: The sulfur-containing asphalt is provided, wherein the sulfur content of the sulfur-containing asphalt is 0.8% to 10%, and wherein the intracyclic sulfur accounts for 70% to 95% of the total sulfur by mass in the sulfur-containing asphalt; The sulfur-containing asphalt is subjected to a series of treatments, including pre-oxidation, low-temperature carbonization, and high-temperature carbonization, with the temperature increasing sequentially, to obtain the hard carbon material.

5. The preparation method according to claim 4, characterized in that, The residual carbon content of the sulfur-containing asphalt is ≥40%; The softening point of the sulfur-containing asphalt is 100℃~300℃; The ash content of the sulfur-containing asphalt is ≤5%; The magnetic content of the sulfur-containing asphalt is ≤10ppm.

6. The preparation method according to claim 4 or 5, characterized in that, The method for preparing sulfur-containing asphalt includes: Provide sulfur-containing oil products, wherein the sulfur content of the sulfur-containing oil products is 0.88% to 10%; The sulfur-containing oil is subjected to heat treatment to obtain the sulfur-containing asphalt.

7. The preparation method according to claim 6, characterized in that, The sulfur-containing oil products may include one or more of the following: high-sulfur residual oil, high-sulfur oil slurry, high-sulfur wax oil, and high-sulfur coal tar. The heat treatment is carried out in an oxygen-containing atmosphere; The heat treatment includes: a preheating treatment and a reaction heat treatment performed in sequence with progressively increasing temperatures; the temperature of the preheating treatment is 100℃~200℃, and the time of the preheating treatment is 1h~3h; the temperature of the reaction heat treatment is 250℃~350℃, and the time of the reaction heat treatment is 2h~5h.

8. The preparation method according to claim 4, characterized in that, The pre-oxidation treatment includes introducing oxygen-containing gas at a volumetric flow rate of 5 L to 20 L / min; the temperature of the pre-oxidation treatment is 200℃ to 300℃; and the time of the pre-oxidation treatment is 3 h to 20 h. The temperature of the low-temperature carbonization treatment is 400℃~700℃, and the time of the low-temperature carbonization treatment is 0.5h~4h; The high-temperature carbonization treatment is carried out at a temperature of 1100℃ to 1400℃ for a duration of 0.5h to 4h.

9. An electrode, characterized in that, The electrode material includes the hard carbon material as described in any one of claims 1 to 3, or the electrode material includes the hard carbon material prepared by the method for preparing hard carbon material as described in any one of claims 4 to 8.

10. A battery, characterized in that, The negative electrode includes a material comprising the hard carbon material as described in any one of claims 1 to 3, or a material comprising a hard carbon material prepared by the method for preparing hard carbon material as described in any one of claims 4 to 8, or an electrode as described in claim 9.